Legal Regulation of Civil Liability for Environmental Damage: How Appropriate are Civil Liability Provisions with the Privacy of Environmental Damage? - AL-KHALAILEH, Lana; AL-BILLEH, Tareq; MANASRA, Majd; ALKHSEILAT, Abdullah; ALZYOUD, Noor; AL-KHAWAJAH, Noor (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).02, 2023)
The study analyzes the nature of civil liability resulting from environmental damage, because the risk of environmental pollution is one of the dangers that cannot be counted or predicted. Therefore, it is difficult to determine the legal basis on which it is based in the field of pollution. Traditional wrong-based liability rules do not respond to the tort-based environmental policy objectives in order to avoid environmental damage and ensure effective protection for those affected. This made the provisions of civil liability in the Jordanian Civil Law no longer commensurate with the specificity of environmental damage, especially since the situation requires compensation for damage to the environment itself and to the health and property of individuals. In addition, it is not hidden that there are shortcomings in the provisions of the Jordanian Environment Protection Law No. (6) of 2017. Its provisions included preventive and remedial measures for environmental pollution without considering the issue of compensation for environmental damage in a manner consistent with the nature and specificity of this damage. This requires the development of these rules in a way that commensurate with the nature of environmental damage.